2017
DOI: 10.1007/s00216-017-0449-9
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography–mass spectrometry methods for the intracellular determination of drugs and their metabolites: a focus on antiviral drugs

Abstract: Understanding the efficacy and/or toxicity of most drugs requires effective intracellular measurements of the drug and its metabolites. Nevertheless, the most common plasma marker of the biological effect of the drug is the area under the curve. Compared with drug determination in whole blood or urine, various difficulties occur in the development of analytical methods for intracellular measurements. We propose step-by-step guidelines to develop an analytical method exploring intracellular concentrations of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 155 publications
0
2
0
Order By: Relevance
“…At the regulatory level, specific OECD test guidelines (TG) based on zfe assays have been recently adopted either to determine acute toxicity (fish embryotoxicity assay, TG N°236) (OCDE 2013) or endocrine activity of xenobiotics acting as an agonist of estrogen receptors (EASZY assay, TG 250) (Brion et al 2019;Pinto et al 2019). Although these assays provide relevant information on the hazard of xenobiotics, a better characterization of their toxicity or endocrine effects requires accounting for the toxicokinetic processes of the active test substance in the whole organism but also in target tissues (Péry et al 2013) and even in cells (Billat and Saint-Marcoux 2017). In this regard, it is important to consider the spatiotemporal estimation of internal concentrations in a biological model that is undergoing rapid morphological and physiological changes during the first 120 h post-fertilization (hpf).…”
Section: Introductionmentioning
confidence: 99%
“…At the regulatory level, specific OECD test guidelines (TG) based on zfe assays have been recently adopted either to determine acute toxicity (fish embryotoxicity assay, TG N°236) (OCDE 2013) or endocrine activity of xenobiotics acting as an agonist of estrogen receptors (EASZY assay, TG 250) (Brion et al 2019;Pinto et al 2019). Although these assays provide relevant information on the hazard of xenobiotics, a better characterization of their toxicity or endocrine effects requires accounting for the toxicokinetic processes of the active test substance in the whole organism but also in target tissues (Péry et al 2013) and even in cells (Billat and Saint-Marcoux 2017). In this regard, it is important to consider the spatiotemporal estimation of internal concentrations in a biological model that is undergoing rapid morphological and physiological changes during the first 120 h post-fertilization (hpf).…”
Section: Introductionmentioning
confidence: 99%
“…Achieving the same effect on the WT protein with a PPI inhibitor would require [I]/ K i of 25, that is, a concentration of drug 25‐fold higher than the dissociation constant. Since antiviral drugs can reach intracellular concentrations of tens of micromolars (Billat & Saint‐Marcoux, 2017 ), the dissociation constant, K i , of the PPI inhibitor should be less than 400 nM to destabilize the WT dimer to the same level as G11S. Meanwhile, several PPI inhibitors that entered clinical trials have reported IC 50 values of around 1 nM or less (Cossar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%